BISKUIT FORMULASI DAUN KELOR (MORINGA OLEIFERA) DAN IKAN KEMBUNG (RASTRELLIGER BRACHYSOMA) TERHADAP PENINGKATAN BERAT BADAN DAN TINGGI BADAN BAYI DUA TAHUN DENGAN STUNTING - Yusnidaryani, Yusnidaryani; Marlina, Marlina; Agustina, Fitriani (Indonesian Trust Health Journal, 2023)
Stunting is a major child health problem in Indonesia. Aceh is a province that is still a locus for stunting. Even though at the end of 2021 the prevalence of stunting in Aceh decreased significantly, the government is still trying to overcome it. Moringa leaves and mackerel are believed to have high benefits for the growth and development process of children. This study aims to identify the effect of biscuits from a formulation of moringa leaf flour (Moringa Oleifera) and mackerel (Rastrelliger Brachysoma) on increasing body weight and height in stunting clowns. This type of research is a quasi-experiment with a one group pre-test and post-test design. The variables used were the formulation of Moringa leaf flour and mackerel into biscuits, and anthropometric data in the form of weight and height of a two-year-old baby. The sample was 45 babies with stunting. Data analysis used t dependent with a significant degree of p value < 0.05. The research results showed that the average increase in body weight was 1.7 ± 0.53 and the average increase in height was 9.71 ± 4.01, the results of the bivariate test showed that biscuits formulated with Moringa leaves and puffed fish had a significant effect on weight gain with a p-value of 0.001 (<0.05) and increase in height. with a p-value of 0.000 (<0.05). In conclusion, there was a significant increase in body weight and height of stunted clowns who received biscuits formulated with moringa leaf flour and mackerel. Abstrak Stunting masih menjadi masalah utama kesehatan anak di Indonesia. Aceh merupakan provinsi yang masih menjadi locus stunting. Walaupun pada akhrir tahun 2021 prevalensi stunting di Aceh menurun secara signifikan, pemerintah tetap berupaya untuk mengatasinya. Daun kelor dan ikan kembung dipercaya memiliki manfaat yang tinggi untuk proses tumbuh kembang anak. Penelitian ini bertujuan Untuk mengidentifikasi pengaruh biskuit dari formulasi tepung daun kelor (Moringa Oleifera) dan ikan kembung (Rastrelliger Brachysoma) terhadap peningkatan berat badan dan tinggi badan pada baduta stunting. Jenis penelitian ini adalah quasi-experiment dengan desain one group pre test dan post test. Variabel yang digunakan adalah formulasi tepung daun kelor dan ikan kembung menjadi biskuit, dan data antoropometri berupa berat badan serta tinggi badan bayi dua tahun. Sampel adalah bayi dua tahun dengan stunting berjumlah 45 baduta. Analisis data menggunakan t dependent dengan derajat signifikan p value < 0.05. Hasil penelitian rerata peningkatan berat badan 1.7 ±0.53 dan rerata peningkatan tinggi badan 9.71 ±4.01, hasil uji bivariat bahwa biskuit formulasi daun kelor dan ikan gembung ada pengaruh yang signifikan terhadap kenaikan berat badan dengan p-value 0.001 (<0.05) dan kenaikan tinggi badan dengan p-value 0.000 (<0.05). Kesimpulan, terdapat peningkatan berat badan dan tinggi badan baduta stunting secara signifikan yang mendapatkan biskuit formulasi tepung daun kelor dan ikan kembung.